The Effects of Hydroxyapatite on the Corrosion Behaviour of AZ Series Mg Alloys - Say, Yakup (Fırat Üniversitesi, 2023)
Metallic biomaterials are widely used in the orthopedic and dental applications owing to their advanced biocompatibility and sophisticated mechanical properties. Many studies are carried out to develop new alloys with high specific strength, high corrosion resistance and high biocompatibility as an alternative to present metallic biomaterials. Mg alloys are potential alloys as a biomaterial, especially because they have low density and high biocompatibility. However, especially the corrosion properties of Mg alloys need to be improved. In this study, the surfaces of AZ31, AZ61 and AZ91 alloys, which are promising as biomaterials, were coated with hydroxyapatite with high biocompatibility, and the effects of the bioceramics coatings on corrosion resistance were comprehensively investigated. Crack-free and porous surface morphologies were obtained in all bioceramic coatings and the presence of the coatings on the surfaces was supported by EDS analysis. As a result of the corrosion tests performed in SBF, it was determined that the AZ91 alloy had the highest corrosion resistance among the uncoated samples. The hydroxyapatite bioceramic coatings also improved the corrosion properties of all samples. However, among all samples, the highest corrosion resistance was obtained in the hydroxyapatite coated AZ91 alloy.
Keywords: Engineering; Mühendislik